Ensuring Constitutional Rights: Legal Protection for Outsourced Workers at PT. MBS (Mie Gacoan) - Saputra, Hendra; Hayatuddin, Khalisah; Mahfus, Abdul Latif; Wulandari, Rina Dwi (Jurnal Hukum Magnum Opus, 2025)
Workers who carry out work in outsourcing companies should not lose their rights, which are protected by the Constitution. Such guarantees and protection cannot be implemented properly only through binding work agreements between companies and workers because workers are in a weak bargaining position as a result of the large number of job seekers or oversupply of labor. The implementation of the outsourcing system is considered to be widely practiced in order to reduce the cost of workers' wages with minimal protection for workers. Moreover, Law No.11/2020 further legalizes the existence of outsourcing and the types of work that are not restricted. Further provisions governing outsourcing are stipulated in Government Regulation No. 35/2021, which stipulates that the working relationship between outsourcing companies and the workers/laborers employed is based on PKWT or PKWTT. The practice of outsourcing is not in accordance with the prevailing laws and regulations, for example at PT MBS (Mie Gacoan) in relation to the protection of wages, welfare, labor social security, occupational safety and health protection, which is not fulfilled by the employer, so that it is very contrary to the law and the responsibility of the state to be able to guarantee that workers obtain their rights. From the results of the research, it was found that after the enactment of the Job Creation Law and Government Regulation Number 35 of 2021, Article 64 and Article 65 of the Manpower Law were abolished and the regulation on the provision of worker/labor services in Article 66 was changed to a regulation on the working relationship between outsourcing companies and the workers/laborers they employ. The provisions in Law No. 11 of 2020 on Job Creation allow for no time limit for outsourced workers, so that workers can be outsourced indefinitely and even for life, such as the sociological facts of outsourced workers at PT MBS (Mie Gacoan) related to protection regarding wages, welfare, labor social security, occupational safety and health protection are not fulfilled by the employer so that it is very contrary to the law and the responsibility of the state to be able to guarantee that workers obtain their basic rights in accordance with the provisions in Article 27 paragraph (2) of the 1945 Constitution and Article 28 D paragraph (2) of the 1945 Constitution.